Field-theoretical renormalization group analysis for the scaling exponents of star polymers - von Ferber, Ch.; Holovatch, Yu. (Condensed Matter Physics, 2002)
We review recent results of the field theoretical renormalization group analysis
on the scaling properties of star polymers. We give a brief account of
how the numerical values of the exponents governing the scaling of star
polymers were obtained as well as provide some examples of the phenomena
governed by these exponents. In particular we treat the interaction
between star polymers in a good solvent, the Brownian motion near absorbing
polymers, and diffusion-controlled reactions involving polymers. Зроблено огляд недавніх результатів аналізу методом теоретикопольової ренормалізаційної групи масштабних (скейлінґових) властивостей зіркових полімерів. Коротко пояснено, як були отримані чисельні значення показників скейлінґу зіркових полімерів. Приведено
приклади явищ, які описуються цими показниками. Зокрема, розглядається взаємодія міз зірковими полімерами у доброму розчиннику, бровнівський рух біля полімерного абсорбера, керовані дифузією
реакції за участю полімерів.